Building a shed : expert advice from start to finish - Truini, Joseph (Taunton's build like a pro., 2002)
From a potting shed or a lean-to tool locker to a storage barn or a workshop, this book shows you how to build a range of domestic outbuildings. It provides you with a range of shed options and the advice you need to design the right structure and to build it from the ground up. Sound construction techniques and time-saving tips ensure that the structure goes up quickly. With plenty of professional advice, you will get the details you want in an outbuilding that you will enjoy for years to come. - Designing a shed to match your needs - Constructing shed foundations - - Selecting framing and finishing materials for economy and durability - - Completing floor, wall and roof framing quickly and accurately - - Building stairways and ramps - Installing windows and doors - * In full colour throughout, with over 500 step-by-step colour photographs and illustrations. * Taunton's Build Like a Pro series: expert advice from start to finish, for a range of home improvement projects. The books offer professional level advice in a format that amateur DIY enthusiasts can appreciate.